Illumination-size relationships of 109 coexisting tropical forest tree species - Sheil, D; Salim, A; Chave, JR; Vanclay, J; Hawthorne, W (2006)
1 Competition for light is a central issue in ecological questions concerning forest tree differentiation and diversity. Here, using 213 106 individual stem records derived from a national survey in Ghana, West Africa, we examine the relationship between relative crown exposure, ontogeny and phylogeny for 109 canopy species. 2 We use a generalized linear model (GLM) framework to allow interspecific comparisons of crown exposure that control for stem-size. For each species, a multinomial response model is used to describe the probabilities of the relative canopy illumination classes as a function of stem diameter. 3 In general, and for all larger stems, canopy-exposure increases with diameter. Five species have size-related exposure patterns that reveal local minima above 5 cm d.b.h., but only one, Panda oleosa, shows a local maximum at a low diameter. 4 The pattern of species exposures at 10 cm diameter is consistent with two overlapping groups, of which the smaller (21 species, including most pioneers) is generally better exposed. 5 Relative illumination rankings amongst species are significantly maintained over a wide range of stem sizes. Species that are well exposed at small diameters are therefore also more likely to be well exposed at larger diameters, although two species in the most exposed 25% of species at 10 cm d.b.h. drop to the lowest illumination quartile at 40 cm d.b.h., and three demonstrate the opposite (low-to-high) pattern. 6 Species capable of achieving the largest diameters are generally recorded less frequently in shade than are smaller species, even when compared as saplings, suggesting that species achieving large mature sizes are generally shade intolerant when small. Controlling for phylogeny reveals that this relationship holds across independent lineages. 7 We also find evidence that the range of strategies encountered is influenced by disturbance regimes. 8 We interpret our results as indicating a continuum of strategies that reflect an evolutionary trade-off between a species' mature size and its general shade-tolerance, in combination with differentiation based on disturbance based opportunities. Species that appear similar can therefore remain ecologically distinct over their lifetimes. © 2006 British Ecological Society.